Neuromuscular performance of Bandal Chagui: Comparison of subelite and elite taekwondo athletes - Moreira, Pedro Vieira Sarmet [UNESP]; Goethel, Márcio Fagundes [UNESP]; Gonçalves, Mauro [UNESP] (Elsevier, 2016)
With the aim of comparing kinematic and neuromuscular parameters of Bandal Chagui kicks between 7 elite and 7 subelite taekwondo athletes, nine Bandal Chaguis were performed at maximal effort in a selective reaction time design, simulating the frequency of kicks observed in taekwondo competitions. Linear and angular leg velocities were recorded through 3D motion capture system. Ground reaction forces (GRF) were evaluated by a force platform, and surface electromyographic (sEMG) signals were evaluated in the vastus lateralis, biceps femoris, rectus femoris, tensor fasciae lata, adductor magnus, gluteus maximus, gluteus medius, and gastrocnemius lateralis muscles of the kicking leg. sEMG data were processed to obtain the cocontraction indices (CI) of antagonist vs. overall (agonist and antagonist) muscle activity. CI was measured for the hip and knee, in flexion and extension, and for hip abduction. Premotor, reaction (kinetic and kinematic), and kicking times were evaluated. Timing parameters, except kinetic reaction time, were faster in elite athletes. Furthermore, CI and angular velocity during knee extension, foot and knee linear velocity, and horizontal GRF were significantly higher in elite than in subelite athletes. In conclusion, selected biomechanical parameters of Bandal Chagui appear to be useful in controlling the training status of the kick and in orienting the training goal of black belt competitors.
Keywords: Cocontraction; Ground reaction force; Kinematic; Martial arts; Roundhouse kick; Velocity